Proteolytic Processing and Activation of Clostridium perfringens Epsilon Toxin by Caprine Small Intestinal Contents - John C. Freedman (American Society for Microbiology, 2014)
ABSTRACT Epsilon toxin (ETX), a pore-forming toxin produced by type B and D strains of Clostridium perfringens, mediates severe enterotoxemia in livestock and possibly plays a role in human disease. During enterotoxemia, the nearly inactive ETX prototoxin is produced in the intestines but then must be activated by proteolytic processing. The current study sought to examine ETX prototoxin processing and activation ex vivo using the intestinal contents of a goat, a natural host species for ETX-mediated disease. First, this study showed that the prototoxin has a KEIS N-terminal sequence with a molecular mass of 33,054 Da. When the activation of ETX prototoxin ex vivo by goat small intestinal contents was assessed by SDS-PAGE, the prototoxin was processed in a stepwise fashion into an ~27-kDa band or higher-molecular-mass material that could be toxin oligomers. Purified ETX corresponding to the ~27-kDa band was cytotoxic. When it was biochemically characterized by mass spectrometry, the copresence of three ETX species, each with different C-terminal residues, was identified in the purified ~27-kDa ETX preparation. Cytotoxicity of each of the three ETX species was then demonstrated using recombinant DNA approaches. Serine protease inhibitors blocked the initial proteotoxin processing, while carboxypeptidase inhibitors blocked further processing events. Taken together, this study provides important new insights indicating that, in the intestinal lumen, serine protease (including trypsin and possibly chymotrypsin) initiates the processing of the prototoxin but other proteases, including carboxypeptidases, then process the prototoxin into multiple active and stable species. IMPORTANCE Processing and activation by intestinal proteases is a prerequisite for ETX-induced toxicity. Previous studies had characterized the activation of ETX using only arbitrarily chosen amounts of purified trypsin and/or chymotrypsin. Therefore, the current study examined ETX activation ex vivo by natural host intestinal contents. These analyses demonstrated that (i) ETX processing in host intestinal contents occurs in an ordered, stepwise fashion, (ii) processing of prototoxin by host intestinal contents results in higher-molecular-mass material and 3 distinct ~27-kDa ETX species, and (iii) serine proteases, such as trypsin, chymotrypsin, and other proteases, including carboxypeptidases, play a role in the activation of ETX by intestinal contents. These studies provide new insights into the activation and processing of ETX and demonstrate that this process is more complicated than previously appreciated.